Prognostic Factors of Outcome in Patients Undergoing Surgical Intervention following Traumatic Intracerebral Haemorrhage - Md Shah Newaz; Md Rabiul Karim; Mohammad Humayun Rashid; SM Noman Khaled Chowdhury; Mohammad Sanaullah; Mahfujul Quader; Tapas Sarker; Sirajul Munir Ohi; Narayan Dhar; Abul Hasan Md Touhidur Reza; Md Kamal Hossain; Asiful Islam (Bangladesh Journal of Neurosurgery, 2024)
Background: Intracerebral hemorrhage is a common complication after traumatic brain injury. While it is accepted practice to remove extra-axial (extradural and subdural) haematoma following traumatic brain injury, but surgical practice in the treatment of traumatic intracerebral hemorrhage (TICH) differs widely, and prognostic factors associated with outcome following surgery have not yet been well established. Aims: The study aimed to determine the prognostic factors of outcome in patients undergoing surgical intervention following traumatic intracerebral hemorrhage in a tertiary care hospital in southeastern part of Bangladesh. Materials and Methods: This prospective interventional study included 45 patients requiring craniotomies for decompression and evacuation of an intracranial hemorrhage following traumatic intracerebral hemorrhage in the Neurosurgery Department of Chittagong Medical College Hospital between December 2021 to June 2023. Demographic features, perioperative clinical and radiological characteristics of these patients were examined in relation to favorable/good outcome, defined as Glasgow Outcome Scale (GOS) score >3 at 3months follow-up, and unfavorable/poor outcome, defined as 3months mortality or GOS score d”3 at 3months after surgery. Results: The median age was 45 (range 8-75) years, 82.2% were male, and road traffic accident was the commonest cause (73.3%). Initial loss of consciousness was found in 75.7% of patients and the median GCS on admission was 9 (Interquartile range 8-10). Craniotomy and evacuation was done in 23(51.1%) of the cases, followed by craniectomy and evacuation in 22 (48.9%)patients. In-hospital and 3 months mortality rate was 28.9%. At three months post surgery, all of the survived patients(32) had good outcomes; 29 (92.3%) had GOS scores of 5, while the remaining 3 had GOS scores of 4. In bivariate analysis, age, history of comorbidity and loss of consciousness, GCS on admission, hematoma volume, and injury to surgery interval was found to have significant association with poor outcome (p<0.05). Age (OR: 1.211, 95% CI: 1.012-1.241, p=0.009) and GCS score on admission (OR: 0.301, 95% CI: 0.086-0.827, p=0.004) were independent predictors of 3-months poor outcome or mortality in multivariate logistic regression analysis. Conclusions: This study presented that older age(60 years) and lower GCS(7-10) on admission were the independent predictors of poor outcome after 3 months of surgery. Multicenter studies are needed to provide accurate data on traumatic intracerebral hemorrhage in Bangladesh. Bang. J Neurosurgery 2024; 13(2): 104-111